Patient-reported outcomes with nivolumab in advanced solid cancers. (November 2018) - Tykodi, Scott S.; Schadendorf, Dirk; Cella, David; Reck, Martin; Harrington, Kevin; Wagner, Samuel; Shaw, James W.
Highlights: PROs reported from eight nivolumab trials in four types of advanced cancer. PROs were assessed using generic, cancer-specific, and tumor type–specific measures. Nivolumab generally sustained/improved HRQoL, and improved functioning. Nivolumab benefits versus chemotherapy or targeted therapy seen across tumor types. PROs may be a differentiating factor between PD-1 inhibitors and other treatments. Abstract: Patients with recurrent or metastatic cancer commonly suffer from debilitating toxicity associated with conventional treatment modalities, as well as disease-related symptoms, often with a concomitant negative impact on health-related quality of life (HRQoL). Patient-reported outcomes (PROs) provide important insights into the patient experience in clinical trials. Nivolumab is a programmed death-1 receptor inhibitor that extends survival in patients with recurrent or metastatic disease in multiple tumor types. In this review, we summarize published PRO analyses from eight phase II–IV clinical trials with nivolumab for the treatment of melanoma, non-small cell lung cancer, renal cell carcinoma (RCC), and squamous cell carcinoma of the head and neck (SCCHN). Symptom burden, physical functioning, and HRQoL were measured using generic, cancer-specific, and tumor type–specific validated PRO instruments. Nivolumab showed sustained stabilization across all tumor types and, in some cases, clinically meaningful improvement in HRQoL, whereas standard of care therapies often led to deteriorations. Exploratory analyses found a positive correlation between baseline HRQoL scores and overall survival in RCC, and between baseline HRQoL scores and healthcare resource utilization in SCCHN, suggesting that patient-reported symptoms at treatment initiation may have clinical value. In the era of value-based oncology care, stakeholders are increasingly interested in PRO findings to guide clinical, regulatory, and reimbursement decisions. However, missing data remain a significant challenge in PRO analyses, including in nivolumab trials. Future clinical trials in immuno-oncology should incorporate PRO data collection, including beyond treatment discontinuation or trial completion to assess the long-term effects of treatment on HRQoL.